THE URGENCY OF PRAYER IN TAFSIR NUR AL-IHSAN BY SHEIKH MUHAMMAD SAID AL-QADHI: NUSANTARA’S INTERPRETATION STUDIES - Sakova, Leddy Humaira; Rusmana, Dadan (State Islamic University of Datokarama Palu, 2022)
Abstract. This study aims to discuss the interpretation of the urgency of prayer in the book of commentary on Nur al-Ihsan by Sheikh Muhammad Said Al-Qadhi. This research method uses a qualitative approach through library-based methods. The results of this study found that in this context the study of quality prayers, namely prayers imbued with Ihsan, has urgency that is relevant to the portrait of prayer that is close to the demands of the message of the Qur'an and the sunnah of the Prophet. The discussion of this research is that the study only focuses on the analysis of surah al-Baqarah in Tafsir Nur al-Ihsan written by Muhammad Said Umar in 1925. The conclusion of this study, prayer is an important worship of other worship. This research is expected to provide benefits for students of knowledge so that they can always obtain useful knowledge.